Implementation of The Relocation Policy For Residents of Rempang & Galang Old Villages: Human Rights Protection Issues - Manullang, Rizky Ariftama; Shahrullah , Rina Shahriyani; Situmeang, Ampuan (Dinasti Research, 2025)
The relocation policy for residents of the Old Villages of Rempang and Galang in the context of developing Rempang Eco City raises serious issues in legal, social, and human rights aspects. This study aims to analyze the implementation of the relocation policy based on the approaches of Ius Constitutum and Ius Operatum, as well as to provide policy recommendations through the framework of Ius Constituendum. The method applied is empirical juridical with a qualitative approach, involving interviews with affected communities and NGOs, as well as a review of relevant legal regulations. The findings show that the relocation policy has not fulfilled the principles of public participation, the right to housing, and social justice, while also neglecting the principle of Free, Prior, and Informed Consent (FPIC), which is a standard in the protection of indigenous peoples. The relocation process is considered to lack transparency, compensation is disproportionate, and it fails to ensure the social and cultural sustainability of local communities. This study emphasizes the need for a human rights–based and justice-oriented relocation policy, referring to John Rawls’ Theory of Social Justice, by ensuring the protection of customary land rights, meaningful participation, and recognition of indigenous cultural identity. The reformulation of the relocation policy should be grounded in legal principles that are humanistic, participatory, and uphold substantive justice.